Asset prices and banking distress: A macroeconomic approach - von Peter, Goetz (Journal of Financial Stability, 2009)
This paper links banking with asset prices in a dynamic macroeconomic model, to provide a simple characterization of financial instability. In contrast with historical bank runs, recent banking crises were driven by deteriorating bank assets. Hence, in contrast with bank run models, this paper focuses on the interaction of falling asset prices, bank losses, credit contraction and bankruptcies. This interaction can explain credit crunches, financial instability, and banking crises, either as fundamental or as self-fulfilling outcomes. The model distinguishes between macroeconomic and financial stability. Its simplicity helps understand balance sheet effects and delivers closed-form solutions without resorting to linearization. For instance, the critical threshold beyond which an asset price decline triggers financial instability can be related explicitly to the structural parameters of the economy.